Актуальні питання реформи децентралізації та адміністративно-територіального устрою - Бородіна, О.А. (Вісник економічної науки України, 2021)
Досвід реформ у зарубіжних країнах свідчить, що саме децентралізація є суттєвим фактором демократизації та модернізації економіки, передбачає конкретні кроки з покращення якості життя, має чіткі рамки та концептуальне наповнення.
Саме децентралізація публічного управління є драйвером формування сприятливого регіонального економічного простору для досягнення сталого розвитку.
Реформи адміністративно-територіального уст-рою останнього часу і в Україні були докорінними та структуроутворюючими, але й попри безліч переваг, розкрили масштабний комплекс проблем, що стосуються взаємовідносин нових рівнів публічної влади та розподілу бюджетних коштів.
Матеріалами статті констатовано, що чинне законодавство поки не пристосоване до нової системи територіального устрою. Потребують нормативних змін та моніторингу питання оптимальної взаємодії органів державної влади та місцевого самоврядування, синхронізації розвитку територіальних рівнів економіки в умовах децентралізації.
Практика продемонструвала, що стейкхолдерами реформи на 95% є муніципалітети, громади, якім потрібні: діалог як запорука довіри, реформа бюджетних відносин, та забезпечення соціальних пріоритетів розвитку громад.
Запропоновано низку положень щодо вдосконалення відносин між рівнями субнаціональних органів управління, ефективності діяльності інститут префектів, розподілу місцевих фінансів, законодавчого унормування аспектів роботи місцевого самоврядування. Опыт реформ в зарубежных странах свидетельствует, что именно децентрализация является существенным фактором демократизации и модернизации экономики, предусматривает конкретные шаги по улучшению качества жизни, имеет четкие рамки и концептуальное наполнение.
Именно децентрализация публичного управления является драйвером формирования благоприятного регионального экономического пространства для достижения устойчивого развития.
Реформы административно-территориального устройства последнего времени и в Украине были основополагающими и структурообразующими, но и, несмотря на множество преимуществ, раскрыли масштабный комплекс проблем, касающихся взаимоотношений новых уровней публичной власти и распределения бюджетных средств.
Материалами статьи констатировано, что действующее законодательство Украины пока не приспособлено к новой системе территориального устройства. Требуют нормативных изменений и мониторинга вопроса оптимального взаимодействия органов государственной власти и местного самоуправления, синхронизации развития территориальных уровней экономики в условиях децентрализации.
Практика продемонстрировала, что стейкхолдерами реформы на 95% являются муниципалитеты, общины, которым нужны: диалог как залог доверия, реформа бюджетных отношений и обеспечения социальных приоритетов развития общин.
Предложен ряд положений по совершенствованию отношений между уровнями субнациональных органов управления, эффективности деятельности институт префектов, распределения местных финансов, законодательного нормирования аспектов работы местного самоуправления. The experience of reforms in foreign countries shows that decentralization is an essential factor in democratizing and modernizing the economy, provides for concrete steps to improve the quality of life, has a clear framework and conceptual content.
It is the decentralization of Public Administration that is the driving force behind the creation of a favorable regional economic space for achieving sustainable development.
Reforms of the administrative-territorial structure in Ukraine have recently been fundamental, structureforming in nature, but, despite many advantages, they have revealed a large-scale complex of problems related to the relationship between new levels of state power and the distribution of budget funds.
The materials of the article indicate that the current legislation has not yet been adapted to the new system of territorial structure. Issues of optimal interaction between state and local government bodies, synchronization of the development of territorial levels of the economy in the context of decentralization require regulatory changes and monitoring.
For the effective completion of reforms, important steps are needed that will allow achieving the conceptual goal of the reform: the government and all authorities must serve the interests of society and ensure the sustainable development of the country. To do this, you need to form an appropriate policy and implement it systematically. It is proposed to adopt new agreements that will allow launching the work of administrations in new districts in a new format. At the same time, it is necessary to adopt a law on the administrative-territorial structure, which will establish rules by which it will be possible to further modernize districts and correct mistakes made. Finally, it is necessary to amend the Constitution in terms of local self-government and territorial organization of power.
A number of provisions are proposed aimed at improving relations between the levels of subnational authorities, improving the efficiency of the Institute of prefects, distributing local finances, and legislative regulation of aspects of local self-government work.